2004
DOI: 10.1055/s-2004-831169
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis Using Diastereotopic Groups

Abstract: Two constitutionally identical but topologically different groups in a chiral molecule are diastereotopic. Selective modification of one of these groups creates one or several new stereogenic centres. This method of stereoselective synthesis that has been used on several occasions is reviewed here. The intention is to focus on an area of stereoselective synthesis that is still underdeveloped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The selectivity achieved in the reaction of this substrate suggests, however, that similar selectivities might be achievable in a diastereotopos-differentiating reaction. [23] In order to study this phenomenon a limited set of 1,3-divinyl-2-cyclopentyl tetronates 8 was synthesized in unoptimized reaction sequences (Scheme 3) and subjected to the conditions of the [2 + 2]-photocycloaddition (Scheme 4). Diacetate 19 was available as side product of the nucleophilic epoxide ringopening of epoxide 12.…”
Section: Preparation Of Key Intermediate 5 and Photocycloaddition Expmentioning
confidence: 99%
“…The selectivity achieved in the reaction of this substrate suggests, however, that similar selectivities might be achievable in a diastereotopos-differentiating reaction. [23] In order to study this phenomenon a limited set of 1,3-divinyl-2-cyclopentyl tetronates 8 was synthesized in unoptimized reaction sequences (Scheme 3) and subjected to the conditions of the [2 + 2]-photocycloaddition (Scheme 4). Diacetate 19 was available as side product of the nucleophilic epoxide ringopening of epoxide 12.…”
Section: Preparation Of Key Intermediate 5 and Photocycloaddition Expmentioning
confidence: 99%
“…As outlined in figure 2, trienes might be Cssymmetric and contain two enantiotopic vinyl moieties, pseudo-C2-symmetric or C1-symmetric (both containing two diastereotopic vinyl groups). Thus, the olefin metathesis step may become a group selective reaction [35,36] in all three cases and this stereochemical problem needs to be addressed. …”
Section: Synthesis Of Heterocycles By Rcm Of Trienesmentioning
confidence: 99%
“…The same group described two different approaches to the tetracyclic core of the aspidosperma alkaloids by a double oxidative amination and double conjugate addition process [29]. Treating the cyclohexadiene 48 with Pd(OAc) 2 and O 2 in DMSO provided the tetracyclic compound 49 as a single isomer in 75% yield. On the other hand, the allylic oxidation using Pd/C-t-BuOOH and subsequent double 1,4-addition in the presence of DBU led to 50 in 54% yield (Scheme 17).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…A broad range of reactions have been developed for the desymmetrization of cyclohexadienes, and synthetic applications to natural product synthesis have been reported. The reviews on the desymmetrization of dienes before 2005 have already been reported [1][2][3][4]. We will then highlight the recent reports for the desymmetrization of dienes by diastereotopic group differentiating reactions in a stereoselective manner and its applications (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation